Influence of structural disordering on phonon and electron spectra of Cu₆₊δPS₅Br superionic crystals - Studenyak, I.P.; Stefanovich, V.O.; Bilanchuk, V.V.; Panko, V.V.; Studenyak, Ya.I. (Functional Materials, 2004)
Raman scattering and optical absorption edge have been studied in Cu₆+δPS₅Br crystals obtained at various technological conditions providing increased copper content and deviation from stoichiometry. The most noticeable changes of Cu₆₊δPS₅Br crystal Raman spectra are revealed in the low-frequency range (v < 100 cm⁻¹) where the modes are observed belonging to the diffusive-type vibrations of Cu atoms and Cu-Br bond vibrations. The temperature studies (77-325 K) of the optical absorption edge have shown that in the superionic phase it is characterized by Urbach shape, copper content increase resulting in the increase of its energy width. A correlation between the degree of static structural disorder and the deviation from stoichiometry in Cu₆+δPS₅Br crystals is revealed. Исследовано комбинационное рассеяние (KP) света и край оптического поглощения кристаллов Cu₆₊δPS₅Br, полученных при различных технологических условиях, предусматривающих увеличение содержания меди и отклонение от стехиометрии. Наиболее заметные изменения спектров KP кристаллов Cu₆+δPS₅Br обнаружены в низкочастотной области (v < 100 см⁻¹), в которой наблюдаются моды, относящиеся к диффузионному типу колебаний атомов Cu и колебаниям связей Cu-Br. Температурные исследования (77-325 K) края оптического поглощения показали, что в суперионной фазе он имеет урбаховскую форму, причем увеличение содержания меди приводит к увеличению его энергетической ширины. Установлена корреляционная связь между степенью статического структурного разупорядочения и мерой отклонения от стехиометрии в кристаллах Cu₆+δPS₅Br. Досліджєно комбінаційнє розсіювання (КР) світла i край оптичного поглинання кристалів Cu₆+δS₅Br, отриманих у різних тєхнологічних умовах, що пєрєдбачають збільшєння вмісту міді та відхилєння від стєхіомєтрії. Найбільш помітні зміни спєктрів КР кристалів Cu₆+δPS₅Br виявлєно у низькочастотній області (v < 100 см⁻¹), в якій спостєрігаються моди, що налєжать до дифузійного типу коливань атомів Cu та коливань зв’язків Cu-Br. Тємпєратурні досліджєння (77-325 K) краю оптичного поглинання показали, що у супєріонній фазі він має урбахівську форму, причому збільшєння вмісту міді приводить до збільшєння його єнєргєтичної ширини. Встановлєно корєляційний зв’язок між ступєнєм статичного структурного розупорядкування та мірою відхилєння від стєхіомєтрії у кристалах Cu₆₊δPS₅Br.